Active Aging of the Elderly in Urban Area, Chiang Mai Province - Orbom, Pitchawee; Traisaeng, Apichart; Chaytaweep, Saowalak; Vongverapant, Metree; Nunta, Piyaphun (Journal of Nurses Association of Thailand Northern Office, 2023)
The objectives of this research were to determine the level of active aging and to study the factors associated with active aging among elderly in urban area, Chiang Mai province. The sample consisted of 395 elderly who live in urban area, Chiang Mai province with ADL score above 12. The research instruments consisted of active aging questionnaires and factors associated with active aging questionnaires, which consisted of social and culture, psychology, health behaviors, and health literacy. The data were analyzed using descriptive statistics and Stepwise Multiple Regression Analysis.The result of this study reveals that active aging of the elderly in urban area, Chiang Mai province were at a good level. The results of factor analysis reveal that active aging in urban area, Chiang Mai province were health literacy (b = 0.89, p < .05), health behaviors (b = 1.58, p < .01), social and culture (b = 1.62, p < .01), and psychology (b = 1.17, p < .01) respectively. This can significantly explain the variation of active aging in the elderly by 76 percent. This research reports the factors associated with active aging in urban area, Chiang Mai province. The results can be useful for elderly to be aware of and prepare for the good and quality active aging in the future.